Immune recognition of lysyl-tRNA synthetase and isoleucyl-tRNA synthetase by anti-OJ antibody-positive sera. Issue 122 (August 2021) - Muro, Yoshinao; Yamano, Yasuhiko; Yoshida, Ken; Oto, Yohsuke; Nakajima, Kimiko; Mitsuma, Teruyuki; Kikuchi, Shiori; Matsumae, Akihiro; Ogawa-Momohara, Mariko; Takeichi, Takuya; Kondoh, Yasuhiro; Katayama, Masao; et al.
Abstract: Objective: Anti -aminoacyl-tRNA synthetase (anti-ARS) antibodies are useful for identifying a clinical subset of patients with idiopathic inflammatory myopathies (IIMs). Anti -OJ antibodies, which recognize multi-enzyme synthetase complexes including isoleucyl-tRNA synthetase (IARS) and lysyl-tRNA synthetase (KARS), are among the anti-ARS antibodies. Although testing antibodies to other ARSs have been used clinically, no validated immunoassays for detecting anti -OJ antibodies are available. We aimed to establish an anti -OJ ELISA. Methods: Serum samples were collected from 279 patients with IIMs and 22 patients with idiopathic interstitial pneumonia. Sixty-four of the samples that had been confirmed to be negative for anti -OJ by standard immunoprecipitation were used as the negative control, and 12 anti -OJ-positive reference sera were used as the positive control. Antibodies to IARS and KARS were assayed by ELISA using biotinylated recombinant proteins generated by in vitro transcription/translation. Results: The anti -OJ-positive sera strongly reacted with the KARS and IARS recombinant proteins in ELISA. Although all 12 reference sera were positive in the anti -KARS ELISA, 4 of the 64 anti -OJ-negative sera were also weakly positive. The sensitivity and the specificity were 100% and 93.8%, respectively. Since our anti -KARS ELISA performed well, showing a high agreement with the results for immunoprecipitation (Cohen's κ > 0.8), the remaining 237 samples were also tested. Thirteen anti -KARS-positive sera were newly found by ELISA, all of which were anti -OJ positive by immunoprecipitation. Conclusion: Immunoassays for detecting anti -OJ antibodies using KARS and IARS recombinant proteins were developed. Our ELISAs performed well, with very high agreement of the results by immunoprecipitation and can be applied to the first reliable, easy-to-use measurement assays for anti -OJ antibodies. Highlights: In vitro translated recombinant isoleucyl/lysyl tRNA synthetases were used in ELISA. The ELISA results correlated well with anti -OJ antibody immunoprecipitation results. In vitro translated recombinants were useful for detecting anti -OJ antibodies.